A aventura narrativa da Telltale Games: um estudo de caso de Game of Thrones – A Telltale Games Series - Bisson, Camila Brandão (2020)
Adventure games, as a genre defined in the context of electronic games, have had throughout their history evolutions and transformations that allowed more, and more, complex stories to be told through video games. The objective of this work starts from a macro analysis, bringing the history of adventure games as a genre, and then, in a second moment, analyzes the style and trajectory of one of the main companies recognized as a reference in the production of narrative games, Telltale Games, starting from a panorama that begins in the history of its predecessor, LucasArts, and ends in the analysis of the particular characteristics of the games produced by the company. From this context, the objective is to carry out a specific analysis of one of the company's titles: Game of Thrones - A Telltale Games Series. It is with the construction of such an analysis that it will be possible to understand how adventure games have effectively evolved as a genre and how narrative and gameplay come together around building an experience based on the player's choices and the development of the story told by the game in question.